Students' Way of Life and Academic Performance During the COVID-19 Pandemic - Vanessa Salomon Maghanoy; Myiella R. Adolfo (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2023)
In order to understand how a student's way of life may affect their academic performance and conduct when studying online, this study looks at the relationship between the two. This study used quantitative correlational research to determine the respondents' academic achievement and way of life during COVID-19. The research participants in this study were chosen via stratified sampling, and standardized questionnaires were made available via a Google form. Since the p-values are more significant than the 0.05 level, the results show no correlation between the respondents' way of life and academic performance. This indicates that the student's way of life has little bearing on how well they succeed academically. When the students are classified according to their personality type profiles, there is a noticeable variation in their way of life. This implies that the student’s way of life varies depending on their personality types.